Factors associated with CIN2–3 recurrence: A single center retrospective analysis - Zhuo-Yi Li; Kai Wang; Xiao-Ling Shen; Qing Li (Human Vaccines & Immunotherapeutics)
Cervical intraepithelial neoplasia, grade 2–3 (CIN2–3), classified as histologic high-grade squamous intraepithelial lesion (HSIL), is associated with a higher recurrence rate and an increased risk of developing cervical cancer. The predictive and influencing factors for CIN2+ relapse are still uncertain and controversial. This study aims to further clarify the risk factors of CIN 2–3 recurrence. The retrospective cohort study enrolled 142 patients with CIN 2–3, aged between 20 to 60 years, all of whom received treatments to remove the lesions. All patients were followed for at least two years to assess outcomes. The primary outcome indicators were high-risk HPV (HR-HPV) status and cervical lesions status within two years after treatment. Fisher’s exact test or Pearson’s chi-squared test and the Kruskal-Wallis (K-W/H) test were used for univariate analysis. Logistic regression analysis was applied to identify independent risk factors, and the results were presented using a forest plot. The study found no significant differences in basic characteristics and HR-HPV status, except for parity (p = .020). HPV genotype before treatment and margin status were significantly associated with cervical lesion status after treatment, with P-values of 0.003 and 0.031, respectively. Cytology before treatment and HPV vaccination were independent factors influencing cervical lesions status two years after treatment, with odds ratios (OR) of 0.634 (95% CI: 0.443–0.908) and 0.340 (95% CI: 0.121–0.952), respectively. This study is the first to report independent factors influencing CIN 2–3 recurrence and underscores the importance of considering adjuvant HPV vaccination for women with cervical preinvasive disease.